Examination of marine and vegetable oil oxidation data from a multi-year, third-party database. (15th July 2018) - De Boer, Anna A.; Ismail, Adam; Marshall, Keri; Bannenberg, Gerard; Yan, Kevin L.; Rowe, William J.
Highlights: Fish oil products from a large database largely meet regulatory oxidation limits. Fish oil products have oxidation results comparable to other dietary oils. Some flavourings can interfere with the p-anisidine value method in oils. Abstract: Fish oil (FO) products constitute good sources of omega-3 fats. Oxidation data from a large third-party database of 1900 + globally-sourced FO samples were assessed. In FO products, for peroxide value (PV), 13.9% exceeded 5 mEq O2 /kg (2.2% >10); for acid value (AcV) 2.1% exceeded 3 mg KOH/g, while for p-anisidine value (pAV) in unflavoured oils, 6.1% exceeded 20, (3.8% >30), and 8.8% exceeded TOTOX limits (26). Additionally, we compared FO with other dietary oils. The FO median PV was similar to those of algal and sunflower oils, 4.8-fold greater than krill oil, and 5.2-fold less than extra-virgin olive oil. The median pAV differed non-significantly among oils. The FO median AcV was similar to those of algal and extra-virgin olive oils, 3.4-fold greater than sunflower oil, and 11.9-fold less than krill oil. This study has provided new insight that retail FO products predominantly meet regulatory guidelines and are comparable in oxidative status to other dietary oils.